Conflict Dynamics and Violence Against the Ahmadiyya Community in Lombok - Muhammad Ijlal Sasakki Junaidi (KEDJATI Journal of Islamic Civilization, 2026)
Religious conflict in Indonesia, particularly violence against the Ahmadiyya community in Lombok, is a complex phenomenon shaped by the interaction of theological, social, political, and cultural factors. This study examines the underlying dynamics of the conflict using Kimball's theoretical framework to explore how religious beliefs, authority, and social structures contribute to the persistence of violence. Employing a qualitative approach, the study analyzes the roles of religious truth claims, obedience to religious authority, local political interests, and institutional legitimacy in sustaining discrimination against the Ahmadiyya community. The findings reveal that exclusive truth claims reinforce social boundaries, discourage intergroup dialogue, and legitimize discriminatory practices. Religious authority, when left unchallenged, can facilitate the moral justification of violence, while structural inequalities and local political dynamics further institutionalize exclusion. The study also demonstrates that the conflict is sustained not only by theological differences but also by competing social and political interests embedded within local power relations. These findings suggest that effective conflict resolution requires an integrated approach that combines legal protection, social reconciliation, and public education to strengthen interreligious coexistence and promote a more inclusive culture of tolerance in Lombok.